Cavitation inception and simulation in blade element momentum theory for modelling tidal stream turbines. (June 2013) - Buckland, Hannah C; Masters, Ian; Orme, James AC; Baker, Tim
Blade element momentum theory (BEMT) is an analytical modelling tool that describes the performance of turbines by cross-referencing one-dimensional momentum theory with blade element theory. Each blade is discretised along its length and the dynamic properties of torque and axial force are determined. A compatible cavitation detection model is introduced to indicate any cavitating blade elements. Cavitation occurrence is dependent on proximity to the free surface, the incident flow velocity and inflow angle and the blade cross-section aerofoil shape. The shock waves associated with cavitation can significantly damage the blade surface and reduce performance; therefore, this model is a useful addition to BEMT and can be used in turbine design to minimise cavitation occurrence. The results are validated using the cavitation experiment observations.